Handbook of family therapy : the science and practice of working with families and couples - Sexton, Thomas L., 1953-; Weeks, Gerald R., 1948-; Robbins, Michael S. (Brunner-Routledge, 2003)
The next major reference in the field of family therapy has arrived! The new Handbook of Family Therapy is destined to become a classic, covering the emergent research, theory, and practice in the field over the past decade.